Klasifikasi Emosi Tokoh Kinan dalam Novel Layangan Putus Karya Mommy Asf: Kajian Psikologi Sastra - Novita, Winda Duwi; Harahap, Nurhayati; Riyanto, Bambang (Universitas Nurul Jadid, 2025)
A novel is an imaginative work that tells all aspects of a person's or several characters' life problems. The novel Layangan Putus by Mommy ASF presents a variety of emotional classifications found in each character. The purpose of this study is to reveal the classification of emotions contained in the novel Layangan Putus by Mommy ASF. This study uses a qualitative descriptive method. The data collection technique began by reading the novel Layangan Putus. Furthermore, the data analysis technique in the study uses a literary psychology approach, namely the initial data needs to be read repeatedly to find the data in the novel Layangan Putus by Mommy ASF. The theory used is Daniel Goleman's Theory which proposes a classification of emotions consisting of anger emotions, sadness emotions, fear emotions, pleasure emotions, love emotions, shock emotions, irritation emotions, and embarrassment emotions. The technique of presenting the results of data analysis is descriptive by presenting data in the form of explanations or descriptions. The results of this study resulted in a classification of emotions divided into eight types of emotions, namely anger emotions, sadness emotions, fear emotions, pleasure emotions, surprised emotions, irritated emotions, and embarrassment emotions. There are positive and negative impacts on the emotional classification of Kinan characters in Mommy ASF's novel Layangan Putus, namely independence and rigidity, understanding of self, and priorities for children. Meanwhile, the negative impacts are psychological trauma, impact on children, and social pressure.